Trawl counts of nekton during seasonal migrations of pacific salmon in the North-West Pacific, Bering and Okhotsk Seas in 2022 - A. N. Starovoitov; S. S. Ponomarev (Известия ТИНРО, 2023)
Spatial distribution, abundance and biomass of fish species, cephalopods and jellyfishes are determined in the epipelagic layer on the data of trawl surveys conducted with RV TINRO and RV Professor Kaganovsky in the Pacific waters at Kuril and Commander Islands, western Bering Sea, and Okhotsk Sea in 2022. Modern state of the nekton communities is considered, in particular the state of pink and other species of pacific salmon in summer and autumn seasons. New data on the size-weight composition of pacific salmon are presented; materials for spatial differentiation between their regional groups of pink salmon are available.